Ambition Level and its Relationship to Ego Flexibility among Autistic Children’s Mothers in Southern Governorates in Jordan - Al-khatatneh, Sami Mohsen (Dirasat: Educational Sciences, 2020)
The current study aims to identify the nature of ego flexibility and its relation to ambition level among mothers of children with autism spectrum disorder in Jordanian southern governorates. To achieve the goals of the study, the descriptive research method was used in the present study. A random sample of (98) autistic children’s mothers in Jordanian southern governorates were selected. Two scales were developed by the researcher to collect data. The first scale sought to measure the level of ambition among mothers of children with autism spectrum disorder. It consisted of 35 Likert-like items scored as follows: always (5), often (4), sometimes (3), rarely (2), and never (1). The second scale sought to assess the level of ego flexibility among these mothers. This scale also included 40 Likert-like items with the following response options: strongly agree (5), agree (4), neutral (3), disagree (2), and strongly disagree (1). The psychometric properties of both scales were verified. Results revealed that ego flexibility and ambition levels were at medium level and indicated a relationship between ego flexibility, precognition, creativity, constructing relationships and ambition. In light of the results, the researcher recommends the necessity to work on developing ego flexibility, in particular constructing relationships among autistic children’s mothers. Also, further research on children with autism spectrum disorder and their mothers in Jordan is needed.